Упровадження сучасних підходів та методів управління конфліктами на промисловому підприємстві - Ровенська, В. В.; Rovenska, V. V. (Класичний приватний університет, 2021)
У статті визначено основні джерела та причини виникнення організаційних конфліктів, а також розглянуто основні технології регулювання конфлікту. Виявлено, що конфлікт виступає необхідною формою взаємодії між його учасниками й є засобом вирішення ключових проблем. З’ясовано неоднозначність впливу конфлікту на мотивацію працівників та систему соціально-трудових відносин на підприємстві. Представлено мапу побудови управлінських конфліктів промислового підприємства Доведено необхідність формування у сучасних працівників кофліктологічної компетентності та конфліктологічної культури. Визначено способи врегулювання управлінських конфліктів на промисловому підприємстві. Доведено, що сьогодні на промислових підприємствах переважають такі проблеми врегулювання конфліктів: відсутність бажання до кооперації; перенесення відповідальності за рішення проблеми на інших працівників; якщо рішення настільки незначні, що не слід витрачати сили на їхню зміну. Спільне обговорення проблем та потреб сторін спрацьовує у ситуаціях, де рішення є важливим для обох сторін; якщо стосунки з партнерами довготривалі й корисні; якщо є час і можливість попрацювати над подальшим розв’язанням складної ситуації; якщо бажання обох сторін збігаються; якщо між партнерами є статусна рівновага (стиль співпраці).

The article identifies the main sources and causes of orga-nizational conflicts, as well as the main technologies of conflict management. Conflict has been found to be an important form of human interaction and a means of solving many problems. The ambiguity of the impact of the conflict on the labor behavior of employees and the system of social and labor relations in the organization has been clarified. The map of construction of man-agerial conflicts of the industrial enterprise is presented. Necessi-ty of formation at modern workers of conflictological competence and conflictological culture is proved. Ways to resolve managerial conflicts at an industrial enterprise are identified. In general, the process of conflict management is a subsystem of enterprise man-agement and is implemented with a dominant functional approach in enterprise management by planning, motivating, controlling and managing conflicts in order to increase the number of rational con-sequences and reduce the negative consequences of conflicts. It is proved that today the following problems of conflict resolution prevail at industrial enterprises: lack of desire for cooperation and passivity in defending one’s rights; shifting responsibility for resolv-ing the problem to others works in situations where the intensity of the conflict is high enough and needs to be reduced; if the de-cisions are so insignificant that no effort should be expended to change them. Joint discussion of the problems and needs of the parties works in situations where the solution is important for both parties; if the relationship with partners is long-lasting and useful; if there is time and opportunity to work on further resolution of a difficult situation; if the wishes of both parties coincide; if there is a status balance between the partners (style of cooperation). In the emergence of conflicts, their characteristics such as tension, emo-tionality, etc. are of great importance. At the same time, managers of many industrial enterprises forget that corporate goals should be paramount, not their own ambitions, beliefs, values, positions, problems, etc., because the manager is an employee and, having entered into an agreement with the company, is obliged to meet the goals. and tasks. The choice of the method of resolving the conflict will depend on the position of the party to the conflict in relation to the opponent, which can be: neutral (constructive), ac-tive (hard), diplomatic (soft). The variety of ways depending on the factors of the conflict situation will allow the leaders of the industrial enterprise to reduce the level or prevent the dysfunctional conse-quences of managerial conflicts.
Introduction of modern approaches and methods to conflict management in an industrial enterprise
Keywords: конфлікт; конфліктологічна компетентність; конфліктологічна культура; трудова поведінка; управління конфліктами; технології врегулювання конфлікту; промислове підприємство; людський потенціал; conflict; conflict competence; conflict culture; labor behavior; conflict management; conflict management technologies; industrial enterprise; human potential